Citizenship and human development: experiences of the delegation of United Nations models in the Institute La Salle of Barquisimeto (Mayéutica Revista Científica de Humanidades y Artes, 2021)
Our main objective was to understand the meanings that the student members of the "Delegación de Modelos de Naciones Unidas de la Unidad Educativa Instituto La Salle Barquisimeto " attribute to civic values for the construction of citizenship from the Human Development approach. For this, the work of the Indian philosopher Amartya Sen on the empowerment of capabilities (freedoms to be and to do) of people was taken as a theoretical basis as well as the definitions of citizenship and civic values of the Spanish philosopher Adela Cortina. The study has a qualitative approach and the techniques of the focus group, the semistructured interview and the documentary review were used. As a result, two aspects linked to the process of construction of citizenship in Lasallian philosophy were identified: human quality and the sense of belonging. The students recognized significant aspects of the formation of the United Nations for All program: discourse, argumentation, criticism and the cultivation of friendship. The assessment of democracy and citizenship is closely related to the concepts analyzed.
Keywords: citizenship; civic values; democracy; human development; La Salle Institute